2021
DOI: 10.1093/jmammal/gyaa147
|View full text |Cite
|
Sign up to set email alerts
|

A unique cricetid experiment in the northern high-Andean Páramos deserves tribal recognition

Abstract: While hypsodonty mostly is associated with medium to large body sizes in sigmodontine rodents, high-crowned molars combined with small bodies rarely are recorded. This latter condition is present in Neomicroxus (Sigmodontinae, incertae sedis), a genus of high-Andean cricetids also characterized by a noticeable set of cranial traits, including enlarged turbinals and rostrum, slanting zygomatic plate, and a marked backward displacement of the vertical ramus of the dentary, linked with an enlargement of the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
0
5
0
8
Order By: Relevance
“…A previous study based on a larger taxonomic sample (176 species) showed that the cranio‐mandibular morphology of sigmodontines evolved under regimes more similar to the Brownian Motion than to the Ornstein–Uhlenbeck model (Maestri et al, 2017), even with notable cases of evolutionary convergence related to feeding habits (Missagia et al, 2021; Pardiñas et al, 2021) and with some overlap among distinct habits along the phylomorphospaces (Maestri et al, 2017). The difference between selection models for appendicular and cranio‐mandibular morphologies suggests that ecological and functional pressures might be more influential selective factors in the evolution of the appendicular skeleton than in the evolution of the skull and mandible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study based on a larger taxonomic sample (176 species) showed that the cranio‐mandibular morphology of sigmodontines evolved under regimes more similar to the Brownian Motion than to the Ornstein–Uhlenbeck model (Maestri et al, 2017), even with notable cases of evolutionary convergence related to feeding habits (Missagia et al, 2021; Pardiñas et al, 2021) and with some overlap among distinct habits along the phylomorphospaces (Maestri et al, 2017). The difference between selection models for appendicular and cranio‐mandibular morphologies suggests that ecological and functional pressures might be more influential selective factors in the evolution of the appendicular skeleton than in the evolution of the skull and mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an equivalent explosive acceleration is not evident from morphological structures presumably associated with the exploration of ecological niches, such as the cranium and mandible (Maestri et al, 2017). In view of this, it has been pointed out that the diversification of alimentary habits, which most directly affects cranio‐mandibular morphology, may have not been a key factor for the explosive diversification of sigmodontines in South America (Missagia & Perini, 2018; Pardiñas et al, 2021), and the diversification of locomotor niches, may have played a more relevant role (Maestri et al, 2017). Even so, phenotypic characters of the external morphology, which are supposedly more related to locomotor habits, also did not show evidence of explosive diversification followed by a slowdown in the rate of evolution (Alhajeri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gran parte de estos estudios y algunos posteriores (e.g., Alvarado-Serrano y D'Elía 2013, Marques-Quintela et al 2014, Leite et al 2015, Jayat et al 2016, Jiménez y Pacheco 2016, avanzaron en la comprensión de Akodontini destacando que incluía y podría seguir incluyendo diversidad espuria (e.g., Neomicroxus, erradicado de la tribu por Alvarado-Serrano y D'Elía 2013 y ubicado en su propia tribu por Pardiñas et al 2021).…”
Section: Análisis Filogenéticos Sobre Datos Morfológicosunclassified
“…Si bien el análisis cladístico de 183 caracteres morfológicos (taxones vivientes) fue pobre en su resolución y recuperó solo algunos clados dentro del grupo, estas relaciones resultaron parcialmente consistentes con hipótesis morfológicas previas (e.g., Hershkovitz 1966, Massoia 1980b, Hinojosa et al 1987, Smith y Patton 1999, Pardiñas et al 2009a extienden por sobre el plano anterior de los incisivos, nasales extendidos lateralmente cubriendo la región anterior del premaxilar y placas cigomáticas estrechas y bajas cuyo margen anterior se encuentra inclinado hacia atrás desde la base. En definitiva, un conjunto de rasgos que fue asociado con el morfotipo "hocicudo" ("long-nose"), tal como discutieran recientemente Pardiñas et al (2021). En particular, se destaca la posición de A. mimus, especie tipo del género Microxus que, sobre la base de evidencia exclusivamente molecular, es considerada parte de la sinonimia de Akodon (véase Patton et al 1989, Smith y Patton 1993, D'Elía 2003, Smith y Patton 2007, Barros et al 2009 1921), taxones caracterizados por su mayor hipsodoncia, rasgo más notable al ser comparado con las otras especies de Akodon.…”
Section: Análisis De Los Taxones Parásitosunclassified
See 1 more Smart Citation